Effect of Incorporation of Neem Leaves (Azadirachta indica) on Feed Intake, Water Intake, Digestibility, Rumen Fermentation Parameter, Blood Biochemicals and Nutrient Utilisation in Camel (Camelus dromedarious) - Bablu Verma; R. Nehra; Rajesh Kumar Sawal (Indian Journal of Animal Nutrition, 2023)
In order to evaluate replacement of conventional roughage ration with fresh neem (Azadirachta indica) leaves; Twelve male camels of similar age and body weight were randomly divided into 3 treatment groups (T1, T2 and T3) of 4 each and fed for a period of 13 weeks. T1 control group was fed with groundnut straw and guar straw in 1:1. Whereas, in T2 group basal roughage was replaced with 10% neem leaves and in T3 group basal roughage was replaced with 20% neem leaves (on dry basis). In this study, no significant effect was observed due to replacement of roughage with neem leaves on intake of dry matter, nutrients and water; digestibility of dry matter and organic nutrients; DCP and TDN; rumen fermentation pattern and blood-biochemical indices. However, significant effect of neem leaves incorporation was observed on crude protein intake and egg per gram (EPG) in faeces of animals fed neem leaves. Digestibility of EE and ADF decreased significantly (P≤0.05) when neem leaves were fed at higher levels. Nutritive ratio was also observed to be significantly decrease (P≤0.01) at higher levels. On the basis of results, it could be concluded that when crop residue-based diet was replaced with neem leaves at lower level of 10% gave better results in terms of dry matter, crude protein and nutritive ratio which could sustain maintenance as ferment ability of diet, decreased at higher level of inclusion. In addition, supplementation of neem leaves could help to be also used as natural and low-cost anti-parasitic feed supplement which is abundantly available. Key word: - Camel, Neem leaves, Digestibility, Rumen fermentation parameters, Nutrient utilization